Novel approach in the construction of bioethanol-producing Saccharomyces cerevisiae hybrids - Štafa, Anamarija (Array, 2019)
Bioethanol production from lignocellulosic hydrolysates requires a producer strain that tolerates both the presence of growth and fermentation inhibitors and high ethanol concentrations. Therefore, we constructed heterozygous intraspecies hybrid diploids of Saccharomyces cerevisiae by crossing two natural S. cerevisiae isolates, YIIc17_E5 and UWOPS87-2421, a good ethanol producer found in wine and a strain from the flower of the cactus Opuntia megacantha resistant to inhibitors found in lignocellulosic hydrolysates, respectively. Hybrids grew faster than parental strains in the absence and in the presence of acetic and levulinic acids and 2-furaldehyde, inhibitors frequently found in lignocellulosic hydrolysates, and the overexpression of YAP1 gene increased their survival. Furthermore, although originating from the same parental strains, hybrids displayed different fermentative potential in a CO2 production test, suggesting genetic variability that could be used for further selection of desirable traits. Therefore, our results suggest that the construction of intraspecies hybrids coupled with the use of genetic engineering techniques is a promising approach for improvement or development of new biotechnologically relevant strains of S. cerevisiae. Moreover, it was found that the success of gene targeting (gene targeting fidelity) in natural S. cerevisiae isolates (YIIc17_E5α and UWOPS87-2421α) was strikingly lower than in laboratory strains and the most frequent off-targeting event was targeted chromosome duplication.